Effect of Rubber Content on Fatigue Crack Growth Rate under Mode I Loading. Issue 4 (May 2017) - Imanaka, Makoto; Asano, Hiroshi
Rubber-modified adhesives have attracted particular interest recently, owing to their property of dramatically increasing the fracture toughness of adhesively-bonded joints. In many cases, these joints are exposed to cyclic loads, and hence an understanding of the fatigue mechanisms is of paramount importance. This study was conducted to characterize the rubber content-dependent behaviour of rubber-modified epoxy adhesive under cyclic loading. Fatigue crack growth rates under mode I loading were measured using adhesively-bonded double cantilever beam specimens with rubber contents of 0, 5 and 14 wt.%. As a result, in the Paris region, an increase in rubber content reduced the fatigue crack growth rate. Similarly to the Paris region, the fatigue threshold for 5 wt.% was greater than that for 0 wt.%; however, the fatigue threshold of joints with 14 wt.% rubber content was nearly equal to those with 5 wt.%.